Empowerment of the Kusumadewi Women's Farmer Group in Processing Household Organic Waste into Liquid Organic Fertilizer - A. A. S. P. R. Andriani; Luh Suariani; Ni Made Yudiastari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
The Kusumadewi Women's Farmer's Group is experiencing the problem of high production costs to increase the growth and yield of its cultivated plants due to the high cost of chemical fertilizers. This causes the profit obtained to be incompatible with the production costs of group cultivation. The group also complained that they did not understand how to process their household organic waste, causing environmental pollution. Therefore, it is necessary to provide an alternative for processing household organic waste into organic fertilizer that is cheap, easy to make, and at the same time can overcome household organic waste that can pollute the environment. Organic fertilizers have the benefit of increasing the nutrient content needed by plants, increasing plant productivity, and stimulating root, stem, and leaf growth. Organic fertilizers have benefits, loosening and fertilizing the soil. The Kusumadewi Women Farmers Group will be given counseling about the benefits of household organic waste and organic fertilizer, how to process organic waste into organic fertilizer, and how to apply it to cultivated plants. Based on the results of the activity, 70% of partners understand and can independently process organic waste as organic fertilizer, partners can reduce production costs by 25%, partners can reduce organic waste that causes environmental pollution by 80%, partners can increase crop production by 25% so that increase group profits.